Advanced Strategies for Surge and Lightning Protection in Photovoltaic Parks - Valcárcel, Ángel; Lucero-Tenorio, Miriam; Barroso Padilla, Rubén (EASI: Engineering and Applied Sciences in Industry, 2023)
The fundamental theoretical aspects of protecting photovoltaic parks against lightning and overvoltages. From an overview of photovoltaic systems, attention is focused on their ability to generate electricity from solar radiation. Lightning, its occurrence, and associated effects, such as electrical surges, are discussed below. Lightning effects in photovoltaic installations were examined, and thermal, electrodynamic, and combustion-related consequences were described in detail. Electric overvoltage was introduced, dividing it into permanent and temporary, as well as the associated risks. The possible implications of overvoltages on solar farms are analyzed, ranging from economic losses to impacts on life and property. It highlights the critical role of the Earth system as a preventive measure and explains its purposes, classification, and design requirements. The crucial role of grounding devices (Class I and II) and circuit breakers in ensuring adequate protection is explained. The practical application of this information is justified by the need to minimize the risks of lightning and overvoltage, to ensure the safe and efficient operation of photovoltaic parks and, simultaneously, to protect life, property, and economic resources.